2017
DOI: 10.1007/s00262-016-1953-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive myeloid-derived suppressor cells are increased in splenocytes from cancer patients

Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of myeloid cells that are increased in the peripheral blood of cancer patients and limit productive immune responses against tumors. Immunosuppressive MDSCs are well characterized in murine splenic tissue and are found at higher frequencies in spleens of tumor-bearing mice. However, no studies have yet analyzed these cells in parallel human spleens. We hypothesized that MDSCs would be increased in the spleens of human cancer patients, simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 35 publications
(53 reference statements)
1
45
0
Order By: Relevance
“…The macrophages in the red pulp filter blood and recycle iron from erythrocytes. The various immune cells in the white pulp, including B cells, T cells, NK cells, macrophages, and dendritic cells, are able to initiate and regulate innate and acquired immune responses (10,12). It has been speculated that because of the altered hematological and immunological profiles postoperation, asplenic patients have an increased mortality risk regardless of the initial splenectomy indication, compared with the general population (13).…”
Section: Introductionmentioning
confidence: 99%
“…The macrophages in the red pulp filter blood and recycle iron from erythrocytes. The various immune cells in the white pulp, including B cells, T cells, NK cells, macrophages, and dendritic cells, are able to initiate and regulate innate and acquired immune responses (10,12). It has been speculated that because of the altered hematological and immunological profiles postoperation, asplenic patients have an increased mortality risk regardless of the initial splenectomy indication, compared with the general population (13).…”
Section: Introductionmentioning
confidence: 99%
“…The functional significance of this finding is uncertain. Increased splenic granulocytic-MDSCs have been associated with cancer in both humans [32] and mice [33]. This observation may reflect, in part, a consequence of sex hormones regulating differentiation of myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…The spleen, as the most important peripheral immune organ, plays a negative immunologic role in it [7] .…”
Section: Discussionmentioning
confidence: 99%
“…As the spleen is one of the most important peripheral immune organs, splenectomy has been suggested to have an impact on immunological function [7] . Some studies found that people with splenectomy have a higher risk of developing overall cancer, as well as certain site-speci c cancers [8,9] .…”
Section: Introductionmentioning
confidence: 99%